Understanding the association of disability with multimorbidity, and healthcare utilization in India's older adult population: insights from cross-sectional evidence of SAGE-2 - Ritik Agrawal; Abhinav Sinha; Abhinav Sinha; Jogesh Murmu; Srikanta Kanungo; Sanghamitra Pati (Frontiers Media S.A., 2024)
BackgroundLike other low-and middle-income countries, India is undergoing a demographic and epidemiologic shift that has led to a significant rise in the burden of non-communicable diseases (NCDs). Evidence suggests that chronic illnesses and disability are linked but limited studies have explored the association between disability and multimorbidity (simultaneous presence of two or more chronic conditions). Since the magnitude of multimorbidity is becoming a norm, it is prudent to understand the association between these two. We aimed to estimate the association between disability and multimorbidity and assess their healthcare utilization among older adults in India using a nationally representative data.MethodsWe employed data from the second round of World Health Organization's Study on Global AGEing and adult health (SAGE) conducted in 2015. SAGE is a nation-wide survey conducted among a representative sample of older adults aged ≥50 years, a total of 7,118 participants aged ≥50 years were included in the analysis. The main outcome of interest was disability for which we used WHODAS 2.0 scoring scale which ranges from 0 to 100. Descriptive statistics such as frequency and proportion were used to report the characteristics of study population, and prevalence. We performed the univariable followed by multiple ordinal logistic regression to assess the association between disability and multimorbidity, reported as adjusted odds ratio (AOR) with 95% confidence interval (CI) and p-value. Healthcare utilization was presented as frequency and proportion.ResultsThe overall prevalence of disability was found to be 89.0% (95% CI: 88.3-89.8) while that of multimorbidity was 39.7% (95% CI: 35.6-37.8). Most of the participants had moderate followed by mild disability. Hypertension (32.7%) was found to be the most prevalent chronic condition followed by cataract (21.3%). The chances of having disability among multimorbid individuals was AOR: 1.40 (95% CI: 1.13-1.75). Participants having disability and multimorbidity mostly visited private sector followed by public healthcare facilities.ConclusionWe observed that nine out of every 10 individuals had some kind of disability in India. We observed multimorbidity to be associated with disability that signifies the need for including disabilities as a part of NCD program as these factors could be bi-directional. Longitudinal studies for disability will be helpful to better understand and address the growing needs of these individuals.